Relationships Between Guanxi of Mega Individuals, Social Support, and Dual Innovation Performance: The Moderating Effect of Interpersonal Capitalization Competence - Beilei Huang; Jinhua Zhang; Xiyuan Li (SAGE Open)
The purpose of this research is to explore the mechanism by which strong or weak guanxi constructed by mega individuals with interpersonal skills affect incremental or breakthrough innovation performance. Based on the questionnaire of 525 mega individuals, this study has verified that strong guanxi cannot directly affect the incremental innovation performance, but the intermediary variables need Indirect effects of emotional, instrumental, and information support). In addition, the affection support obtained by mega individuals has no positive impact on breakthrough innovation performance. Meanwhile, it is also verified that information support plays a mediating role in weak guanxi and breakthrough innovation performance, as well as in strong guanxi and incremental innovation performance; instrumentality support and affection support play a mediating role in mega individuals strong guanxi and incremental innovation performance; interpersonal capitalization competence has a positive moderating role in between strong guanxi and instrumentality support.